A viscoplastic approach for pore collapse in saturated soft rocks using REDBACK: An open-source parallel simulator for Rock mEchanics with Dissipative feedBACKs. (April 2016) - Poulet, Thomas; Veveakis, Manolis
Abstract: Numerical simulators have become indispensable in geomechanics to model increasingly more complex rock behaviours by harnessing the growing computational power available. Those tools aim at simulating more realistic scenarios while accounting for more physical processes. As such, geomechanical modelling remains particularly challenging because of the inherent multi-scale and multi-physics nature of all physical processes at play. In this context the standard approach of sequential coupling is reaching its limits when dealing with multiple physical processes and is maladapted for the modelling of material instabilities. We present in this study a novel numerical simulator, REDBACK, to model multi-physics Rock mEchanics with Dissipative feedBACKs in a tightly coupled manner. This tool provides both the prototyping flexibility to investigate more complex physics and non-linear feedbacks as well as the computational scalability to tackle three dimensional scenarios. We demonstrate the approach by modelling pore collapse and validating the approach against isotropic consolidation experiments on Bleurwiller sandstone as well as drained triaxial experiments on a diatomaceous mudstone. Through this exercise we identify the activation enthalpy dependency on confining pressure that is required to match the experiments. The results show that dilatancy corresponds to internal processes with negative activation volume, while contractancy corresponds to internal processes with positive activation volume. This calibration process demonstrates the importance of a physics-based approach in a multi-scale framework, where one can aim at extrapolating results outside the range of laboratory experiments based on the understanding of the underlying physical processes, when traditional engineering approaches are often limited to interpolation within the scope of sparse and expensive experiments.